2019
DOI: 10.1097/meg.0000000000001597
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D-related immunomodulation in patients with liver cirrhosis

Abstract: Objective(s) Increasing evidence indicates that vitamin D status is linked to severity of liver cirrhosis and patients’ survival. However, the potential role of vitamin D-related immunomodulation in hepatic decompensation and patients’ mortality in relation to vitamin D deficiency remains unknown. The aim of the current study is to evaluate the association between vitamin D status and vitamin D binding protein (VDBP) levels with serum cytokine and lipopolysaccharide binding protein (LBP) and to exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…VitD Def was highly common in our study cohort, being present in 57% of patients and additional 26% with VitD insufficiency, according to commonly used cut-offs for 25-OH-vitamin D levels [ 10 ]. Of note, comparisons to other studies regarding the prevalence of VitD Def are difficult to draw, as there are considerable differences in cut-offs and patient characteristics, however, other studies have demonstrated similar results [ 11 , 12 ]. As indicated previously, a recent meta-analysis confirmed the association between VitD deficiency and mortality in patients with cirrhosis [ 13 ].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…VitD Def was highly common in our study cohort, being present in 57% of patients and additional 26% with VitD insufficiency, according to commonly used cut-offs for 25-OH-vitamin D levels [ 10 ]. Of note, comparisons to other studies regarding the prevalence of VitD Def are difficult to draw, as there are considerable differences in cut-offs and patient characteristics, however, other studies have demonstrated similar results [ 11 , 12 ]. As indicated previously, a recent meta-analysis confirmed the association between VitD deficiency and mortality in patients with cirrhosis [ 13 ].…”
Section: Discussionmentioning
confidence: 96%
“…Alcohol-related liver disease (ALD; n = 96, 41%) and viral hepatitis (n = 47, 20%) represented the predominant ACLD etiologies. Median HVPG was 18 (12)(13)(14)(15)(16)(17)(18)(19)(20) mmHg, and 202 (86%) patients had clinically significant portal hypertension (CSPH, i.e. an HVPG ≥ 10 mmHg).…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing pieces of evidences indicated that the pathogenesis of liver fibrosis related to the changes in immune function 9,10,35 . It is no doubt that the immunologic reactions response to hepatic fibrosis are complicated and incompletely clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the abnormal changes of hepatic immune microenvironment during hepatic fibrosis attracted increasing attention among foreign and domestic scholars [7][8][9][10] . Indoleamine 2,3-dioxygenase 1 (IDO1), which serves as an immunomodulatory molecule, is an intracellular enzyme that participates in the metabolism of the essential amino acid tryptophan (TRP) in the kynurenine (KYN) pathway [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%